2009
DOI: 10.1111/j.1365-2435.2008.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Predator perches: a visual search perspective

Abstract: Summary 1.Predators hunting by sight often search for prey from elevated perches or hovering positions above the prey habitat. Theory suggests that prey visibility depends strongly on predator perch height and distance, but their quantitative effects have not been experimentally tested in natural habitats. 2. We estimate for the first time how prey visibility depends on predator perch height, distance and vegetation height in an open natural habitat, based on visibility measurements of two targets: a mounted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 58 publications
1
56
1
Order By: Relevance
“…Consequently, owing to the lack of the compact layer of vegetation normally occurring in grasslands, the soil on abandoned farmland was drier. Presumably this is beneficial for some soil-dwelling invertebrates, such as ants, some coleopterans and orthopterans (which are abundant in the diet of the nestling Whinchats we examined), which are also easier to catch on bare ground or in lower vegetation (Andersson et al 2009;Schaub et al 2010). In addition, it should be stressed that Whinchats hunt primarily from a perch, so both the denser vegetation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, owing to the lack of the compact layer of vegetation normally occurring in grasslands, the soil on abandoned farmland was drier. Presumably this is beneficial for some soil-dwelling invertebrates, such as ants, some coleopterans and orthopterans (which are abundant in the diet of the nestling Whinchats we examined), which are also easier to catch on bare ground or in lower vegetation (Andersson et al 2009;Schaub et al 2010). In addition, it should be stressed that Whinchats hunt primarily from a perch, so both the denser vegetation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our dietary analysis showed that for Whinchats soil-dwelling invertebrates tended to be of secondary importance as food because the majority of prey items ([70 % in each age class) were those associated with vegetation. This seems to imply indirectly the importance of a mosaic-like structure of the microhabitat with low vegetation or vegetation-free patches and bare ground, where prey are more accessible and the hunting of foraging Whinchats is more efficient (Bastian et al 1994;Bastian and Bastian 1996;Andersson et al 2009). Lastly, we were able to identify some invertebrate prey items only to the level of class/order (such as Araneae or Lepidoptera larvae), which to some degree hampered a more detailed analysis and the drawing of further inferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fences and posts in this study were of a similar height (~1.25 m tall) and likely used by the owls as perches to increase their field of vision (Andersson et al 2009) and maximize detection of predators. Increased visual detection should shorten response time (Devereux et al 2006) and therefore increase the probability of successfully reacting to a threat (Kenward 1978, Fitz gibbon 1990, Krause & Godin 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Though only available to a small portion of our sample of owls, perches > 2 m tall (power lines and tall shrubs) were not used by any individuals. Larger raptors such as hawks prefer taller perches (Bohall & Collopy 1984, Berkelman et al 2002, Leyhe & Ritchison 2004) because of increased prey visibility (Andersson et al 2009). Increased risk from other raptors is the most likely reason why burrowing owls do not use these taller perches.…”
Section: Discussionmentioning
confidence: 99%